The Moderating Role of Tax Sanctions on the Effect of Tax and Accounting Knowledge on MSME Taxpayer Compliance - Hernando, Riski; Azzahra Hamid, Tsabitah; Leonardo, Ivan; Abdurrahman, Rezi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have consistently played a vital role in Indonesia's economic resilience and in stabilizing the economy amidst national financial instability, particularly during times of crisis. This study investigates the influence of tax knowledge, accounting knowledge, and tax sanctions on MSME taxpayer compliance in Jambi City, Indonesia. Furthermore, it examines whether tax sanctions moderate the relationship between knowledge variables and taxpayer compliance. Employing a quantitative approach, the study collected data from 40 MSME respondents through purposive sampling. Multiple linear regression analysis was used to test the proposed hypotheses. The results indicate that tax knowledge does not significantly affect tax compliance, while accounting knowledge exerts a significant positive influence. Collectively, tax knowledge, accounting knowledge, and tax sanctions significantly affect taxpayer compliance. Additionally, tax sanctions do not moderate the relationship between tax knowledge and tax compliance but do moderate the relationship between accounting knowledge and tax compliance. These findings suggest the importance of strengthening accounting literacy and the strategic implementation of tax sanctions to improve compliance behavior among MSMEs.